A comparative effectiveness study of degludec and insulin glargine 300 U/mL in insulin‐naïve patients with type 2 diabetes - Joseph M. Tibaldi; Martin Hadley‐Brown; Andreas Liebl; Steffen Haldrup; Viktor Sandberg; Michael Lyng Wolden; Helena W. Rodbard (2018)
Aims To compare the real‐world effectiveness of insulin degludec (degludec) and glargine 300 units/mL (glargine U300) in insulin‐naïve adult patients with type 2 diabetes in routine US clinical practice. Materials and methods CONFIRM is a non‐interventional comparative effectiveness study following US patients across the continuum of care, through electronic medical records from multiple health systems and integrated delivery networks. Propensity‐score matching controlled for confounding. The primary endpoint, change in HbA1c from baseline to 180 days of follow‐up, was estimated using a repeated‐measure of covariance analysis with subject as random effect. Change in the rate of hypoglycaemic episodes (defined using International Classification of Diseases codes 9/10) and change in proportion of patients with hypoglycaemia were estimated using negative binomial and logistic regression, respectively. Time‐to‐discontinuation of the initial basal insulin/initiation with another prescribed basal insulin was analysed using a Cox Proportional Hazard model. Results Data concerning 4056 patients were analysed. After matching, baseline characteristics were comparable (n = 2028 in each group). After 180 days of follow‐up, degludec was associated with a larger reduction in HbA1c (estimated treatment difference, −0.27%; P = 0.03), greater reductions in change in rate (rate ratio, 0.70; P < 0.05) and greater reductions in change in the likelihood of hypoglycaemia (odds ratio, 0.64; P < 0.01]) compared with glargine U300. In addition, patients treated with degludec were 27% less likely to discontinue treatment at follow‐up compared with those treated with glargine U300 (hazard ratio, 0.73; P < 0.001). Conclusions Significantly improved HbA1c, larger reductions in rates and likelihood of hypoglycaemia and lower risk of treatment discontinuation were demonstrated with degludec vs glargine U300.